2020
DOI: 10.1038/s41598-020-59427-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Characteristics of Hot Extremes Over India in a Warming Environment and their Driving Mechanisms

Abstract: change in hot extremes is one of the accepted evidence and also a global indicator of an anthropogenic climate change, which has serious environmental and economic impacts. in the present study, the india Meteorological Department gridded temperature data is used to characterize hot extremes over india in terms of frequency and intensity. Results provide compelling evidence that large parts of india, except the Indo-Gangetic plains, have experienced more occurrences of hot days (upsurge by 24.7%) having higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
(87 reference statements)
1
19
1
Order By: Relevance
“…Kothawale et al(2010) examined the trends in pre-monsoon temperature extremes for 121 stations in India and found widespread positive trends in the frequency of hot days and nights, while negative trends were observed for cold days and nights. Similar findings were reported by Dash and Mamgain (2011) for 1969and Revadekar et al(2012) for 1970. Joshi et al(2020 assessed the changing patterns of hot extremes over India and reported that the frequency of hot days has augmented by 24.7% in the recent past compared with the past .…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Kothawale et al(2010) examined the trends in pre-monsoon temperature extremes for 121 stations in India and found widespread positive trends in the frequency of hot days and nights, while negative trends were observed for cold days and nights. Similar findings were reported by Dash and Mamgain (2011) for 1969and Revadekar et al(2012) for 1970. Joshi et al(2020 assessed the changing patterns of hot extremes over India and reported that the frequency of hot days has augmented by 24.7% in the recent past compared with the past .…”
Section: Introductionsupporting
confidence: 79%
“…Changes in the geopotential height anomalies at 500 hPa have been linked to the enhanced prevalence of the hot extremes (Ding et al 2010;Loikith and Broccoli 2012;Lee and Lee 2016). Joshi et al (2020) explored the physical driving mechanisms responsible for the observed increases in the frequency and intensity of hot extremes over the Indian landmass. The study cited that the augmentation of the geopotential height anomalies at 500 hPa over the northern parts of India is leading to increases in hot extremes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Diffenbaugh and Ashfaq, 2010; Loikith and Broccoli, 2012; Lee and Lee, 2016; Hu and Huang, 2020; Joshi et al ., 2020; Pi et al ., 2020; Zhu et al ., 2020) indicate that large‐scale circulation is one of the most vital factors responsible for high‐temperature extremes. Regional and global climate models also show an increase in extreme heat events in the future (Vogel et al ., 2020; Almazroui et al ., 2021; Sambou et al ., 2021; Iyakaremye et al ., 2021b); however, the distribution of changes is not uniform worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…A primary cause for enhancing the frequency, duration and intensity of ExT is anticipated to the global warming, as a response to anthropogenic climate forcing (Baldwin et al, 2019;IPCC, 2021IPCC, , 2014Krishnan et al, 2020). The physical mechanism involved in the formation of such ExT is linked to large-scale atmospheric dynamics as well as regional-scale land-atmosphere interactions (De and Mukhopadhyay, 1998;Ganeshi et al, 2020;Ghatak et al, 2017;Joshi et al, 2020;Ratnam et al, 2016). The atmospherically driven phenomenon such as quasi-stationary Rossby wave-train and El Niño Southern Oscillation originated from the North-Atlantic Ocean and tropical Pacific, respectively, in-turn maintains the warm and dry air thermodynamically at the surface, through the high-pressure system.…”
Section: Introductionmentioning
confidence: 99%